The development of smart apps creator learning media to improve ipas learning outcomes - Reza, Regita Pramesti; Putra, Galih Mahardika Christian (Indonesian Research Journal in Education |IRJE|, 2025)
This research is included in research and development (R&D) by applying the ADDIE model. This research is motivated by the fact that teachers are not optimal in using technology-based learning media. This causes low learning outcomes for the fourth-grade students in the material of my area and its natural wealth. This study aims to test the validity, practicality, and effectiveness of learning materials developed by Smart Apps Creator (SAC) in enhancing learning outcomes. The population involved in this research is the fourth-grade students of SD Negeri Klumprit 04, a total of 32 students. The data collection techniques include test and non-test methods, such as observation, interviews, questionnaires, and documentation. The study results show that the Smart Apps Creator (SAC) learning media was developed with researcher-recorded voiceovers and self-taken images. The feasibility assessment indicates very feasible criteria, with scores from media experts (88%), material experts (83%), students (98%), and teachers (94%). Its effectiveness is demonstrated by a significant improvement in student learning outcomes, with an N-Gain score of 0.7007 (high category).